JCOM 2020
DOI: 10.12788/0019
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Disparities Among Adolescents and Adults With Sickle Cell Disease: A Community-Based Needs Assessment to Inform Intervention Strategies

Abstract: ickle cell disease (SCD), an inherited chronic medical condition, affects about 100,000 individuals in the United States, a population that is predominantly African American. 1 These individuals experience multiple serious and life-threatening complications, most frequently recurrent vaso-occlusive pain episodes, 2 and they require interactions with multidisciplinary specialists from childhood. Because of advances in treatments, the majority are reaching adulthood; however, there is a dearth of adult health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Individuals with SCD reported that access to an SCD specialist (a provider-level barrier) was a key barrier, consistent with prior studies on barriers to care for individuals with SCD [ 16 , 19 , 20 ]. As a patient perspective, this finding stands out in contrast to a recent study reporting provider perspectives from emergency department physicians that patient behavior is the most important barrier to SCD care [ 21 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Individuals with SCD reported that access to an SCD specialist (a provider-level barrier) was a key barrier, consistent with prior studies on barriers to care for individuals with SCD [ 16 , 19 , 20 ]. As a patient perspective, this finding stands out in contrast to a recent study reporting provider perspectives from emergency department physicians that patient behavior is the most important barrier to SCD care [ 21 ].…”
Section: Discussionsupporting
confidence: 79%
“…Difficulty with transportation was a significant challenge, particularly for participants who lived in a community that did not have a sickle cell specialist. Among prior studies investigating barriers to care, transportation was infrequently mentioned by adolescents with SCD as a barrier to clinic attendance [ 18 ] but was more frequently endorsed as a barrier to care among adolescents and adults with SCD in Northern California [ 20 ], suggesting adolescents rely on parents/caregivers for transportation and lack of reliable transportation is a more common barrier among adults with SCD. Insurance-funded transportation was an essential source of support for many participants, but its use still involved overcoming barriers that were not an issue with private transportation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain management during an acute vaso-occlusive episode in a pediatric patient with sickle cell disease (SCD) is challenging to treat and standard-of-care options are limited to opioids, IV fluids, adjunct ketamine infusions, regional anesthesia, and nonsteroidal anti-inflammatory drugs (NSAIDs) [ 1 , 2 , 3 , 4 ]. Acupuncture has long been studied for pain relief, however, a unified theory of its action in Western Medicine has not been accepted [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, acupuncture for the use of pain management in pediatric patients with SCD during an acute pain episode is a vastly understudied area of medicine [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has long been studied for pain relief, however, a unified theory of its action in Western Medicine has not been accepted [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, acupuncture for the use of pain management in pediatric patients with SCD during an acute pain episode is a vastly understudied area of medicine [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%